Application of Habituation and Singing Methods in Forming Character Religious and Moral Values in Early Childhood - Intan Lestari; Zusy Aryanti (Universitas Islam negeri Mahmud Yunus Batusangkar, 2024)
This research aims to describe the process of character formation with religious and moral values through habituation and singing methods. The approach used in the research is descriptive qualitative with data collection techniques of observation, interviews and documentation. Data analysis which includes data reduction, data presentation, and drawing conclusions. Testing the validity of the data uses triangulation techniques, namely technical triangulation and source triangulation. The results of the research show that the habituation and singing method allows children to directly model what they can and cannot do. So that children get used to doing something that is good and easy to remember or sticks in the child's memory and will become a habit that forms character, religious and moral values. These two methods also make learning activities more interesting, not boring and monotonous for children.